Restorative Justice: A Modern Approach to Criminal Law and Conflict Resolution - Syauqi Askolani (ASIAN PUBLISHER, 2024)
Restorative justice represents a transformative shift in the philosophy of criminal law by focusing on healing, accountability, and the restoration of relationships rather than punitive measures. Unlike traditional justice systems that prioritize punishment, restorative justice empowers victims, offenders, and communities to engage in meaningful dialogue aimed at addressing the harm caused by criminal behavior. This approach fosters empathy, encourages offender accountability, and promotes long-term reconciliation. As societies face the limitations of retributive justice, restorative practices are increasingly recognized as effective tools for conflict resolution, especially in cases involving youth, minor offenses, and community disputes. This article explores the principles, implementation strategies, and global impact of restorative justice, highlighting its potential to reshape legal norms and enhance the justice system’s responsiveness to human needs.